Spousal communication, changes in partner attitude, and contraceptive use among the Yorubas of Southwest Nigeria - Ogunjuyigbe Peter; Ojofeitimi Ebenezer; Liasu Ayotunde (Indian Journal of Community Medicine, 2009)
Objective: This paper highlights the relevance of spousal communication on males′ attitude towards their partners′ contraceptive use. Design: This was a cross-sectional study. Materials and Methods: Data for the study were obtained from a survey carried out in three states, Oyo, Osun, and Ondo, mainly inhabited by the Yorubas. Results: The results show that men have a significant role to play in the adoption of contraception. About 37% of the respondents reported joint decision making on when to have another child, 40.8% on whether to stop having children, and 44% on what to do to stop childbearing. Communication between a husband and wife on reproductive matters was also recognized as a factor that may influence male participation in family planning. Conclusion: This study has shown that the male partner may be highly motivated to obtain contraceptives. The results therefore suggest that male involvement in family planning should be encouraged through inter-spousal communication.